PROSPECTS OF REGULATING MEDIA RESOURCES ON TELEGRAM: UKRAINIAN EXPERIENCE - Kateryna Horska (Інтегровані комунікації, 2025)
The article examines the structure of the Ukrainian media landscape on the Telegram platform in the context of a full-scale war and the prospects for its regulation. The study is based on the monitoring of 288 Telegram channels in the News and Media category.